The Influence of School Culture on the Motivation of High School Students in Yogyakarta - Ahmad Chandra Jaya; Eni Agustina; Agus Basuki; Putri Luthfiyah Zahra; Listriasa Jihad Insani (Journal of Innovation in Educational and Cultural Research, 2024)
Background on school culture is one factor that influences students to increase learning motivation. A healthy school culture provides opportunities for school members to function optimally, work efficiently, be full of vitality, have high spirits, and be able to continue to grow. This study aims to collect empirical evidence or facts about the influence of school culture on student learning motivation by looking at the influence between school culture and student learning motivation. This research methodology uses a quantitative approach with a correlational research design. Because the data distribution is close to the normal curve, the sample of this study consists of 100 students. The results showed a significant relationship with a positive correlation of 0.512. This study concludes that school culture and student learning motivation have a significant positive relationship. The contribution of this study is that it can be used as a resource to help create an educational climate that is more aware of the importance of education.